Autopsy findings of coronary artery disease- A 6-month study in rural tertiary care centre (Journal of Pathology of Nepal, 2024)
Background:  Atherosclerosis is a general term used for all conditions involving thickening and hardening of arterial walls. Atherosclerosis is the most common and important type of coronary artery disease. In almost all developed countries and  India the prevalence and incidence of ischemic heart disease is increasing. The objective of the present study was to examine the coronary tree, study grades of atherosclerosis, complications of atherosclerosis like plaque disruption, inflammation, and calcification, and identify the severity of atherosclerosis according to age and gender.Materials and methods: This was a retrospective observational study conducted during 6 month period between January 1st 2023, and June 30th 2023. A total of 89 patients of different age groups were brought for postmortem examination. During postmortem examination, the heart was removed and examined. Macroscopic and microscopic changes were noted.Results: Of the 89 cases, 62 were male and 27 were female. Coronary atherosclerosis was present in 69 (77.52%) of the patients. Atherosclerosis was present in 53 men (76.81%) and 16 women (23.18%). Men are affected more than women. The majority of the patients (24.63%) were in the , followed by those in the age group of 31-40 years (21.73%), while (21.73%) were in the 61-70 years age group.Conclusions:  The incidence of atherosclerosis is higher in men. This study highlights the necessity of screening for cardiovascular problems starting in the early thirties.